Banking prudentials, leverage, and innovation partnership choice in China - Luan, Fushu; Chen, Yang; Lang, Lin; Lim, King Yoong (Journal of Banking & Finance, 2025)
In a theoretical context where innovators borrow loans or settle for state-owned enterprise (SOE) sponsorship for their projects, we examine the effects of banking prudential regulations and their interaction with corporate leverage on the patenting partnership choice in China using a unique matched patent-firm-bank loan dataset for 15,623 observations in the 2013–17 period. We use a unique instrumental variable (IV) strategy to identify idiosyncratic bank prudential reform shocks associated with the post-2012 Basel III regulation and find prudential metrics (corporate leverage) of the financiers (firms) to positively (negatively) influence SOE patenting partnership choice, though prudential regulation mitigates the latter. Prudential reforms therefore come at a cost of further SOE dominance. However, conditional on an innovation project being SOE sponsored, we find positive spillover effect from the SOE’s employment mandate to loan productivity. Our results are robust across different IV strategies, alternative measures, sub-sample and mechanism analyses.